Cardiac surgery-associated acute kidney injury: risk factors, pathophysiology and treatment - Wang, Ying; Bellomo, Rinaldo (Nature reviews. Nephrology, 2017)
Key Points CSA-AKI is the second most common cause of AKI in the intensive care setting and is associated with increased mortality The pathophysiology of CSA-AKI is very complex and probably includes renal ischaemia–reperfusion injury, inflammation, oxidative stress, haemolysis and nephrotoxins To date, no consensus definition for CSA-AKI exists, but the KDIGO criteria for AKI are commonly used in clinical practice To date, no pharmacological or non-pharmacological preventive strategies have been shown to reduce the occurrence of CSA-AKI in clinical trials The management of CSA-AKI requires a multifaceted approach Renal replacement therapy is necessary in 1–5% of patients with CSA-AKI and is associated with poor patient and renal prognosis, both in the short and long-term Cardiac surgery-associated acute kidney injury (CSA-AKI) is the most common complication in adult patients undergoing open heart surgery. In this Review, the authors discuss the definition, epidemiology, pathophysiology and risk factors of CSA-AKI. The authors also explore the use of novel biomarkers of AKI and their potential utility in preventing or treating CSA-AKI. Cardiac surgery-associated acute kidney injury (CSA-AKI) is the most common clinically important complication in adult patients undergoing open heart surgery, and is associated with increased mortality and morbidity. In patients in intensive care units, CSA-AKI is the second most common type of AKI after septic AKI. In this Review, we explore the definition of CSA-AKI, discuss its epidemiology and identify its risk factors. We discuss current theories of the pathophysiology of CSA-AKI and describe its clinical course. Furthermore, we introduce diagnostic tools with particular reference to novel biomarkers of AKI and their potential utility; we analyse currently applied interventions aimed at attenuating AKI in patients undergoing cardiac surgery; and describe evidence from randomized controlled trials aimed at preventing or treating CSA-AKI. Finally, we explore issues in the use of renal replacement therapy, its timing, its intensity and its preferred modalities in patients with CSA-AKI, and we discuss the prognosis of CSA-AKI in terms of patient survival and kidney recovery.